Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1016/j.ejso.2021.05.046
|View full text |Cite
|
Sign up to set email alerts
|

Direct surgery with cytoreductive surgery and hyperthermic intraperitoneal chemotherapy for patients with colorectal peritoneal metastases

Abstract: Introduction: Neoadjuvant chemotherapy is widely used in treatment of peritoneal metastases from colorectal cancer, but there is little scientific evidence for this approach. This study aimed to study survival in patients treated with direct surgery with cytoreductive surgery and hyperthermic intraperitoneal chemotherapy (CRS-HIPEC), i.e. without neoadjuvant chemotherapy. Material and methods: Patients with histopathologically confirmed peritoneal metastases from colorectal cancer that underwent first-time CRS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 16 publications
1
5
0
Order By: Relevance
“…It found no survival benefit for CRS HIPEC performed with high-dose oxaliplatin ip and 5-FU/leucovorin iv, except for patients with a peritoneal cancer index of 11–15 in a post-hoc analysis [ 22 ]. The latter point is consistent with a prior finding suggesting that patients with a peritoneal cancer index of up to 16 and/or limited small bowel involvement benefit most from CRS HIPEC [ 96 , 97 , 98 , 99 ]. Much has been written on the strength and weakness of the PRODIGE-7 trial, which was first presented in June 2018 at the American Society of Clinical Oncology meeting and included contemporary systemic chemotherapy and targeted therapy.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…It found no survival benefit for CRS HIPEC performed with high-dose oxaliplatin ip and 5-FU/leucovorin iv, except for patients with a peritoneal cancer index of 11–15 in a post-hoc analysis [ 22 ]. The latter point is consistent with a prior finding suggesting that patients with a peritoneal cancer index of up to 16 and/or limited small bowel involvement benefit most from CRS HIPEC [ 96 , 97 , 98 , 99 ]. Much has been written on the strength and weakness of the PRODIGE-7 trial, which was first presented in June 2018 at the American Society of Clinical Oncology meeting and included contemporary systemic chemotherapy and targeted therapy.…”
Section: Resultssupporting
confidence: 91%
“…In addition, the extension of PC of colorectal origin matters beyond mere resectability with a threshold peritoneal cancer index of 20 and below most commonly reported. Indeed, many expert centers today set the bar for CRS HIPEC at a peritoneal cancer index of 16 [ 96 , 97 , 98 , 99 , 110 , 111 ] to maximize cure, while avoiding large resection of small bowel to prevent a short bowel syndrome. Peritoneal recurrence after CRS HIPEC is common with a median time to recurrence of 33 months [ 112 , 113 , 114 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, to our knowledge, no study has described any gender differences in tumor burden in patients with mCRC. In a recent study on curatively treated patients with CRC with peritoneal metastases there were no gender differences in tumor burden (information from the author) 37 . Another study showed that primary tumor location affected the burden of liver metastases, 38 a factor adjusted for in all multivariable models.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study on curatively treated patients with CRC with peritoneal metastases there were no gender differences in tumor burden (information from the author). 37 Another study showed that primary tumor location affected the burden of liver metastases, 38 a factor adjusted for in all multivariable models. In the present study, there was no gender difference in the presence of multiple metastatic locations, which is in line with a previous study.…”
Section: Discussionmentioning
confidence: 99%
“…30 Similarly from Sweden, a recent retrospective study of 131 consecutive patients reported a median OS of 40 months after complete cytoreduction, with 60% of the study population receiving adjuvant chemotherapy. 31 The authors question the need for NAC due to the favourable reported survival. Perhaps, for the purposes of survival, the timing of systemic chemotherapy is inconsequential.…”
Section: Discussionmentioning
confidence: 99%